Montessori Approach inʿUlūmu al-Qur’āni wa al-Ḥadīṡ Learning at Brainy Bunch, Malaysia - Helmi Aulia Tazky (UPT Publikasi Ilmiah Unisba, 2026)
This study aims to examine the implementation of the Montessori approach in the teaching of ʿUlūmu al-Qur’āni wa al-Ḥadīṡ and its impact on upper elementary students at Brainy Bunch Cyberjaya, Malaysia. This study is based on the need for innovation in Islamic religious education, which is still dominated by conventional approaches and does not sufficiently encourage active student participation. This study employs a descriptive qualitative approach, using data collection techniques such as participant observation, interviews, and documentation. The results of the study indicate that the implementation of the Montessori approach in the teaching of ʿUlūmu al-Qur’āni wa al-Ḥadīṡ is still in the development stage and is not yet supported by specialized equipment. Nevertheless, the basic Montessori principles have been applied in the learning process, as evidenced by the activities carried out during the learning process. These findings indicate an increase in students’ independence, creativity, and contextual understanding of the content of the Qur’an and Hadith. These findings suggest that the Montessori approach has the potential to serve as a pedagogical strategy in Islamic education and can foster a more meaningful learning process.